High Hydrostatic Pressure Processing of Whole Carrots: Effect of Static and Multi-Pulsed Mild Intensity Hydrostatic Pressure Treatments on Bioactive Compounds - Fernando Viacava; Perla A. Ramos-Parra; Jorge Welti-Chanes; Daniel A. Jacobo-Velázquez (Foods, 2021)
In this study, the effects of static and multi-pulsed mild-intensity high hydrostatic pressure (HHP) treatments (60 or 100 MPa, ~23 °C) on the extractability and accumulation of phenolics and carotenoids in whole carrots were evaluated. HHP treatments were applied for the time needed to reach the desired pressure (come-up-time, CUT) either as a single pulse or multi-pulse (2P, 3P, and 4P). Likewise, a single sustained treatment (5 min) applied at 60 or 100 MPa was evaluated. Individual carotenoids, free and bound phenolics were quantified after HHP treatment and subsequent storage (48 h, 15 °C). As an immediate HHP response, phenolic extractability increased by 66.65% and 80.77% in carrots treated with 3P 100 MPa and 4P 60 MPa, respectively. After storage, CUT 60 MPa treatment accumulated free (163.05%) and bound (36.95%) phenolics. Regarding carotenoids, total xanthophylls increased by 27.16% after CUT 60 MPa treatment, whereas no changes were observed after storage. Results indicate that HHP processing of whole carrots at mild conditions is a feasible innovative tool to enhance the nutraceutical properties of whole carrots by increasing their free and bound phenolic content while maintaining carotenoid levels. HHP treated carrots can be used as a new functional food or as raw material for the production of food and beverages with enhanced levels of nutraceuticals.